Lessons from the Islamic movement of the Pesantren in Wali Barokah Kediri - HUMAIDI, A.; FADHLIYAH, N.; AMRULLOH, M.; SAREGAR, A.; ZAHRA, D.N.; MIHMIDATY, Y. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this research is to analyze the background of the founding of Islamic teachings, movements, and social politics. The historical narrative study approach is used. The results found out that the Wali Barokah Islamic Boarding School stands behind the founder who tends to be scripturalist and puritanism. The curriculum is summarized in the Al-Manhaj al-Tarbiyah guidelines. On the other hand, the socio-political movement is as follows: Using the method of proselytizing more softly and openly, as an agent of Da'i-Da'iyah, in collaboration with institutions outside and with economic activities.RESUMEN El propósito de esta investigación es analizar los antecedentes de la fundación de las enseñanzas, movimientos y políticas sociales islámicas. Se utiliza el enfoque del estudio histórico narrativo. Los resultados encontraron que el internado islámico Wali Barokah, respalda al fundador que tiende a ser bíblico y puritano. El plan de estudios se resume en las pautas de Al-Manhaj al-Tarbiyah. Por otro lado, el movimiento sociopolítico es el siguiente: usar el método de proselitismo de manera más suave y abierta, como agente de da'i-da'iyah, en colaboración con instituciones externas y con actividades económicas.